Gastrointestinal symbionts of chimpanzees in Cantanhez National Park, Guinea-Bissau with respect to habitat fragmentation - Sá, Rui (2013)
One of the major factors threatening chimpanzees (Pan troglodytes verus) in Guinea-Bissau is habitat fragmentation. Such fragmentation may cause changes in symbiont dynamics resulting in increased susceptibility to infection, changes in host specificity and virulence. We monitored gastrointestinal symbiotic fauna of three chimpanzee subpopulations living within Cantanhez National Park (CNP) in Guinea Bissau in the areas with different levels of anthropogenic fragmentation. Using standard coproscopical methods (merthiolate-iodine formalin concentration and Sheather's flotation) we examined 102 fecal samples and identified at least 13 different symbiotic genera (Troglodytella abrassarti, Troglocorys cava, Blastocystis spp., Entamoeba spp., Iodamoeba butschlii, Giardia intestinalis, Chilomastix mesnili, Bertiella sp., Probstmayria gombensis, unidentified strongylids, Strongyloides stercoralis, Strongyloides fuelleborni, and Trichuris sp.). The symbiotic fauna of the CNP chimpanzees is comparable to that reported for other wild chimpanzee populations, although CNP chimpanzees have a higher prevalence of Trichuris sp. Symbiont richness was higher in chimpanzee subpopulations living in fragmented forests compared to the community inhabiting continuous forest area. We reported significantly higher prevalence of G. intestinalis in chimpanzees from fragmented areas, which could be attributed to increased contact with humans and livestock.